Generation of onco-enhancer enhances chromosomal remodeling and accelerates tumorigenesis - Chai, Peiwei (Nucleic Acids Res, 2020)
Chromatin remodeling impacts the structural neighborhoods and regulates gene expression. However, the role of enhancer-guided chromatin remodeling in the gene regulation remains unclear. Here, using RNA-seq and ChIP-seq, we identified for the first time that neurotensin (NTS) serves as a key oncogene in uveal melanoma and that CTCF interacts with the upstream enhancer of NTS and orchestrates an 800 kb chromosomal loop between the promoter and enhancer. Intriguingly, this novel CTCF-guided chromatin loop was ubiquitous in a cohort of tumor patients. In addition, a disruption in this chromosomal interaction prevented the histone acetyltransferase EP300 from embedding in the promoter of NTS and resulted in NTS silencing. Most importantly, in vitro and in vivo experiments showed that the ability of tumor formation was significantly suppressed via deletion of the enhancer by CRISPR-Cas9. These studies delineate a novel onco-enhancer guided epigenetic mechanism and provide a promising therapeutic concept for disease therapy.